Development and Function of Immune Cells in an Adolescent Patient With a Deficiency in the Interleukin-10 Receptor. Issue 1 (July 2017) - Veenbergen, Sharon; van Leeuwen, Marieke A.; Driessen, Gertjan J.; Kersseboom, Rogier; de Ruiter, Lilian F.; Raatgeep, Rolien (H.)C.; Lindenbergh-Kortleve, Dicky J.; Simons-Oosterhuis, Ytje; Biermann, Katharina; Halley, Dicky J.J.; de Ridder, Lissy; Escher, Johanna C.; et al.
ABSTRACT: Objective: Monogenic defects in the interleukin-10 (IL-10) pathway are extremely rare and cause infantile-onset inflammatory bowel disease (IBD)-like pathology. Understanding how immune responses are dysregulated in monogenic IBD-like diseases can provide valuable insight in "classical" IBD pathogenesis. Here, we studied long-term immune cell development and function in an adolescent IL-10 receptor ( IL10RA )-deficient patient who presented in infancy with severe colitis and fistulizing perianal disease and is currently treated with immune suppressants. Methods: Biomaterial was collected from the IL10RA -deficient patient, pediatric patients with IBD, and healthy controls. The frequency and phenotype of immune cells were determined in peripheral blood and intestinal biopsies by flow cytometry and immunohistochemistry. Functional changes in monocyte-derived dendritic cells and T cells were assessed by in vitro activation assays. Results: The IL10RA -deficient immune system developed normally with respect to numbers and phenotype of circulating immune cells. Despite normal co-stimulatory molecule expression, bacterial lipopolysaccharide-stimulated monocyte-derived dendritic cells from the IL10RA -deficient patient released increased amounts of tumor necrosis factor α compared to healthy controls. Upon T-cell receptor ligation, IL10RA -deficient peripheral blood mononuclear cells released increased amounts of T-cell cytokines interferon γ and IL-17 agreeing with high numbers of T-bet + and IL-17 + cells in intestinal biopsies taken at disease onset. In vitro, the immunosuppressive drug thalidomide used to treat the patient's decreased peripheral blood mononuclear cell-derived tumor necrosis factor production. Conclusions: With time and during immunosuppressive treatment the IL10RA -deficient immune system develops relatively normally. Upon activation, IL-10 is crucial for controlling excessive inflammatory cytokine release by dendritic cells and preventing interferon γ and IL-17-mediated T-cell responses. Abstract : Supplemental Digital Content is available in the text